2016
DOI: 10.1016/j.nut.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity is associated with early reduction in bone mass in pediatric inflammatory bowel disease

Abstract: Adiposity was associated with reduced bone mass in the early phases of IBD, but with increased bone mass in the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…[7,18,19] In the current study, children with a lower BMI had more osteoporosis in total body and spinal BMD studies (P=0.038 and P=0.039, Saadah et al [13] found that low weight and height Z-scores were associated with the development of osteoporosis in patients with CD, yet low BMI Z-scores were not significantly associated with a low BMD. However, contrary to our findings, Setty-Shah et al [20] concluded that the AP spine BMD Z-score was much lower in obese IBD patients with high levels than in controls. Additionally, Wada et al [21] observed that IBD patients with a high BMI had low BMD levels.…”
Section: Discussioncontrasting
confidence: 99%
“…[7,18,19] In the current study, children with a lower BMI had more osteoporosis in total body and spinal BMD studies (P=0.038 and P=0.039, Saadah et al [13] found that low weight and height Z-scores were associated with the development of osteoporosis in patients with CD, yet low BMI Z-scores were not significantly associated with a low BMD. However, contrary to our findings, Setty-Shah et al [20] concluded that the AP spine BMD Z-score was much lower in obese IBD patients with high levels than in controls. Additionally, Wada et al [21] observed that IBD patients with a high BMI had low BMD levels.…”
Section: Discussioncontrasting
confidence: 99%
“…78 Furthermore, PCDAI was not found to be associated with BMD in 3 cross-sectional studies. 77,79,86 Statement 2.17. Sex, disease location, disease behavior, extraintestinal manifestations, granulomas, and perianal disease do not predict BMD (84% agreement).…”
Section: Supplementary Resultsmentioning
confidence: 99%
“…All 10 studies that examined nutritional status/anthropometrics in relation to reduced BMD reported an association with either lower weight or lower height. 29,[79][80][81][82][83][84][85][86][87] For weight, 9 of 9 studies were positive, 29,[79][80][81][82][83][84][85]87 and for height, 5 of 8 studies were positive, 79,80,83,85,88 whereas 3 were negative. 29,81,87 Importantly, most studies reporting on height were cross-sectional.…”
Section: Prognostic Factors For Surgerymentioning
confidence: 99%
“…Rates of obesity are rising in patients with IBD, as in the general population; 15-40% of adults with IBD are obese, and 20-40% are overweight (18,19). Previous studies showed that the higher adiposity in early life in pediatrics with IBD and also in newly diagnosed IBD patients is signi cantly associated with reduced bone mass, as shown by BMD z-score (20,21).…”
Section: Discussionmentioning
confidence: 99%